Rethinking 'Islamic heritage': two case studies to ponder - Rashid, Md. Mizanur; Abdul Rahim, Asiah (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
Architecture played an instrumental role in spreading ideas of different civilizations around the world. Hence, through documenting heritage we could document the facets of different cultural Diaspora through time and spaces. The objective of the heritage study program at the department of Architecture of HUM is to capture the facets of Islamic Diaspora around the world. As the very concept of Islamic architecture is problematic in today's architectural discourse, whether the buildings that the students are documenting during their visit are true representative of Islamic architecture is an issue to be discussed. During the Heritage Study trip 20 II, the students of architecture ofHUM have recorded two interesting buildings, Haghighi house in Esfahan, Iran and the Diwan-i-Aam of Lalbagh fort, Dhaka, Bangladesh that are apparently 'secular' in tenns of their function. Whether they could be able to elucidate the variegated expressions of Islamic architecture at two seemingly opposite geo-temporal locations is the central research question of this article. By using these two examples, this paper critically reexamines the stereotypical but popular conceptions of 'Islamic Architectural Style' that obscured the historical processes of hybridization and its diverse morphological outcomes, and comprehend the process of resilience and assimilation through which architecture is shaped in a particular context.